Review of the latest results from the Pierre Auger Observatory - Wahlberg, Hernán Pablo (2015)
The Pierre Auger Observatory, located in the province of Mendoza, Argentina, was built for detecting and studying ultra-high energy cosmic rays. The Observatory was designed as a hybrid detector covering an area of 3000 km2 and it has been taking data for more than ten years. In this report a selection of the latest results is presented. These include the observation of the flux evolution and suppression at the highest energies, inferred trends on composition with energy, bounds on photons and neutrinos, and arrival direction studies.